A Smartwatch Integrated with a Paper‐based Microfluidic Patch for Sweat Electrolytes Monitoring. Issue 3 (4th November 2020) - Cao, Qingpeng; Liang, Bo; Mao, Xiyu; Wei, Jinwei; Tu, Tingting; Fang, Lu; Ye, Xuesong
Abstract: Here, a smartwatch for sweat monitoring was presented for perspiration analysis. The smartwatch played the part of analyzing, computing, and displaying the real‐time data with the feature of comfortable wearing and lightweight ergonomic design. Moreover, the paper‐based microfluidic patch with a three‐dimensional structure was proposed to realize the sweat collection and solve the issue of sweat accumulation. To further realizing the sweat monitoring, the potassium and sodium ion‐selective electrodes were developed by the screen‐printing technique. The experiment of on‐body monitoring the K + and Na + in sweat had been carried out to further demonstrate the feasibility of the smartwatch. Abstract :